ISSUES OF VALUES IN ANCIENT PHILOSOPHY - Павло ОБЛАП (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article addresses the issues of values in ancient philosophy. The aim of the study is to analyze and reflect on the views of ancient philosophers on values and to examine their influence on the development of moral philosophy. The following approaches and research methods were used: the historical-philosophical approach – to study the views of ancient philosophers on values in the context of their time; the comparative approach – to compare the views of different philosophers on values; and the analytical approach – to logically analyze key concepts such as the Good, virtue, happiness, justice, etc. It has been established that in the history of European philosophy, the concept of “values,” as an embodiment of the term “the Good” (that which brings benefit), originates in ancient philosophy. Various approaches to understanding values that existed in ancient philosophy are characterized. It is noted that Seneca’s views on values combined key Stoic principles such as virtue and self-control; Plato regarded the Good as the highest value and the goal of human life, linking it to justice both at the individual and societal levels; for Aristotle, the highest value and the goal of human life was happiness, which a person strives for through their actions and moral deeds. It is emphasized that, unlike the Pre-Socratics, who focused on studying the natural world and cosmological questions, the philosophers of classical Greece turned their attention to society and the state, considering that a rational (just, ideal) state is the key to personal well-being. It is demonstrated that questions about the place of a person in the world, their path, the essence of good and evil, and moral guidelines unite Greek and Roman Stoics with the existentialist philosophers of the 20th century. The theoretical significance of the study lies in its ability to analyze the origins of fundamental philosophical categories – Good, virtue, justice, and happiness – and trace their influence on the further development of philosophy. The practical significance lies in the fact that the research materials can be included in lecture courses, allowing students to better understand the origins of modern ethical and moral principles. A promising direction for further research is considered to be the comparison of ancient and modern concepts of values. The article belongs to the theoretical type.